1975
DOI: 10.1677/joe.0.0670275
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotrophin and Steroid Levels Around the Time of First Ovulation in the Rat

Abstract: Luteinizing hormone, FSH, prolactin, oestradiol and progesterone concentrations were measured by radioimmunoassay in the blood of female rats from 7 days before the first ovulation (the day of first ovulation is designated day 0) until the day after the second ovulation. Serum LH concentrations varied between 29 and 59 ng NIAMDD-rat-LH RP-1/ml from days -7 to -2. On the day preceding first ovulation (day -1) a steep increase in serum LH was found between 13.00 h and 15.00 h reaching a maximal value of 2100 ng/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
2

Year Published

1977
1977
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 16 publications
(21 reference statements)
0
34
2
Order By: Relevance
“…In the female, neonatal levels are high in comparison with those of the adult ; they increase between 7 and 25 days of age and then return to adult dioestrous values before vaginal opening. On the evening of first pro-oestrus the rise in FSH concentrations is equivalent to that observed during subsequent preovulatory surges (Meijs-Roelofs et al, 1975b;Parker & Mahesh, 1976;Ojeda et al, 1976 . In our colony, serum LH concentrations Text- fig.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…In the female, neonatal levels are high in comparison with those of the adult ; they increase between 7 and 25 days of age and then return to adult dioestrous values before vaginal opening. On the evening of first pro-oestrus the rise in FSH concentrations is equivalent to that observed during subsequent preovulatory surges (Meijs-Roelofs et al, 1975b;Parker & Mahesh, 1976;Ojeda et al, 1976 . In our colony, serum LH concentrations Text- fig.…”
mentioning
confidence: 77%
“…An investigation of the effects of PMSG treatment on immature rats showed that, rather than increasing the numbers of large follicles, the hormone altered the balance between large and atretic follicles (Peters, Byskov, Lintern-Moore, Faber & Anderson, 1973 (McNatty, Hunter, McNeilly & Sawers, 1975) supported the previous findings and showed that an increase in FSH stimulated the granulosa cells to secrete oestradiol which in turn affected the growth of subsequent follicles (Baird, Baker, McNatty & Neal, 1975 fig. 4), whereas after 21 days of age values decrease and remain consistently low until the first preovulatory rise (Cheng & Johnson, 1974;Meijs-Roelofs et al, 1975b;Ojeda et al, 1976 (Text-fig. 4).…”
mentioning
confidence: 95%
“…In the rat, rising estrogen levels during diestrus are critical for the preovulatory release of GnRH and LH in proestrus and, consequently, the release of eggs during the early hours of estrus [2]. Both basal and GnRH-stimulated LH secretion are strictly dependent on estrogen action on the pituitary [26]. All SERMs used in these experiments reduced both basal and stimulated LH secretion, as did the ‘pure’ anti-estrogen ICI.…”
Section: Discussionmentioning
confidence: 99%
“…On the day of first proestrus, and under the influence of ele vated estrogen levels (1, 50,62] the responsiveness to LHRH increases again and the LHRH 'priming' effect becomes ap parent (20,75]. This facilitatory effect of estradiol (E2) on gonadotropin release can be demonstrated as early as 5 days after birth (86] and the priming effect of LHRH by day 26 [27], Thus, it seems evident that the pituitary gland can re spond to LHRH stimulation with substantial increases in LH release very early in life.…”
Section: The Pituitary Glandmentioning
confidence: 99%